Schizotypy and Performance on an Insight Problem-Solving Task: The Contribution of Persecutory Ideation - Cosgrave, Jan; Haines, Ross; Golodetz, Stuart; Claridge, Gordon; Wulff, Katharina; van Heugten – van der Kloet, Dalena (Frontiers in Psychology, 2018)
Insight problem solving is thought to underpin creative thought as it incorporates both divergent (generating multiple ideas and solutions) and convergent (arriving at the optimal solution) thinking approaches. The current literature on schizotypy and creativity is mixed and requires clarification. An alternate approach was employed by designing an exploratory web-based study using only correlates of schizotypal traits (paranoia, dissociation, cognitive failures, fantasy proneness and unusual sleep experiences) and examining which (if any) predicted optimal performance on an insight problem solving task. 121 participants were recruited online from the general population and completed the Number Reduction Task. The discovery of the hidden rule was used as a measure of insight. Multivariate logistic regression analyses highlighted persecutory ideation to best predict the discovery of the hidden rule (OR=1.05; 95% CI 1.01-1.10, p=0.017), with a one point increase in persecutory ideas corresponding to the participant being 5% more likely to discover the hidden rule. This result suggests that persecutory ideation, above other schizotypy correlates, may be involved in insight problem solving.